Salmon Aquaculture - Lu, Qian (IntechOpen, 2022)
This book discusses the technologies and models of salmon aquaculture. It examines the use of probiotics, the application of recirculation systems, and the addition of high-strength materials in salmon aquaculture. It also discusses the problems hindering the development of salmon aquaculture and proposes potential solutions.